Perbandingan Pemakaian KB Hormonal Terhadap Durasi Kejadian Gangguan Siklus Haid Pada Akeptor KB Di TPMB Siti Jaojiah - Olivia Nency; Ikmah Maulani Ramadhan (Jurnal Keperawatan Muhammadiyah, 2023)
Background: menstrual cycle irregularity is indeed one of the side effects of implanted contraception. Disorders of menstrual patterns are often found, especially in the first 6-12 months and then some women may experience amenorrhea. Based on previous research which stated that hormonal contraception can affect the occurrence of menstrual cycle disorders Purpose of Writing: For Comparison of Use of Hormonal Family Planning Against the Duration of Events of Menstrual Cycle Disturbances in Family Planning Acceptors at TPMB Siti Jaojiah Research Methods: This research is experimental in nature with a quasi-experimental design with pre-test and post-test with a quantitative approach. The location of this research was conducted at TPMB Siti Jaojiah. All KB acceptors use hormonal contraception. The inclusion criteria in this study were willing to be respondents, mothers who were not overweight or obese, mothers who experienced adequate rest and exclusion criteria were not willing to be respondents. This study used a purposive sampling technique. Research Results: Based on statistical tests the Tukey HSD test was carried out on acceptors of hormonal birth control by injection, pills and implants. It was seen that the sinificace value showed p> 0.05, which means that there was no difference between the use of injection contraception, pills and implants on the duration of the event. menstrual cycle. However, seen between injections and implants that have the same duration in the incidence of menstrual cycle disturbances. So that of the three hormonal birth control, the fastest duration of menstrual cycle disturbances was found in the use of injection contraception with a value of 3.64, then implants with a value of 4.67 and pills with a value of 7.70 Conclusions and Suggestions: as information in providing information regarding the selection of contraceptive use, hormonal contraceptives that are the fastest in experiencing menstrual disorders are injections so that the weaknesses of hormonal birth control can be conveyed to the fullest